Unraveling the Role of α2δ‐1 in Cerebral Hemorrhage: Calcium Overload, Endoplasmic Reticulum Stress, and Microglial Apoptosis - Ning Yu; Xiaopeng Li; Bingqian Wang; Chengrui Nan; Qianxu Jin; Liang Yang; Depei Li; Zongmao Zhao (Brain and Behavior)
ABSTRACT Objective Cerebral hemorrhage is a severe condition associated with high morbidity and mortality. Understanding the underlying pathogenesis is crucial for developing effective therapeutic strategies. This study aimed to investigate the role of the dysregulated α2δ‐1 protein in cerebral hemorrhage. Materials and Methods We observed a significant upregulation of α2δ‐1 in cerebral hemorrhage tissue. Knockdown of α2δ‐1 resulted in decreased intracellular calcium concentration and reduced phosphorylation of PLCr and IP3R in the presence of calcium. Additionally, α2δ‐1‐mediated calcium overload induced ERS in BV2 microglia, accompanied with increased phosphorylation of PERK and decreased ERS‐related protein levels. Results α2δ‐1 knockdown significantly inhibited BV2 microglia apoptosis and downregulated apoptosis‐related proteins in the presence of calcium. Our study indicates the involvement of α2δ‐1 in calcium‐mediated signaling, endoplasmic reticulum stress, and BV2 microglia apoptosis. Conclusions The findings provide a basis for considering α2δ‐1 as a potential therapeutic target in cerebral hemorrhage and secondary brain injury conditions associated with calcium dysregulation.